Pengaruh Karakteristik Individu, Karakteristik Pekerjaan dan Karakteristik Lingkungan Terhadap Motivasi Kerja Pegawai Pada Satuan Polisi Pamong Praja Kota Pontianak - Indrawati Indrawati; Aprina Kuswardani (Jurnal Ilmiah Aset, 2019)
Human resource is the most valuable resource and has an increasingly important position in achieving the objectives of the organization. Human is the core driving force of all activities and is also a major part in the processing of the input into the output. This research was conducted in the territory of the city of Pontianak. Independent variables (X) in this study consist of 3 individual characteristics, job characteristics, and environmental characteristics, while dependent variable (Y) is motivation. The data in this study were obtainet from the results of the questionnaire to 34 respondents who also as samples in this research. The data later processed using multiple Linear Regression analysis. The result showed that only one individual characteristics, job charakteristics and environmental characteristics had a significant influence on employee motivation at Civil Service Police Unit Pontianak.